Demonstration of Brain Expansion in Cases of Chronic SDH during Admission Leads to Decreased Rates of Recurrence - Yagnick, Nishant S.; Moolchandani, Sandeep; Sinha, Sumit; Mehta, V. S. (Indian Journal of Neurotrauma, 2019)
While being considered a simple procedure among the wide spectrum of neurosurgical procedures, the surgical management of chronic subdural hematoma (SDH) still possesses a degree of variability. Present concepts of production versus absorption of chronic SDH fluid has led to practitioners differing in the use of drains, the treatment of inner membrane, the flushing of the subdural cavity, and the perioperative decision making for cases with comorbidities and a history of anticoagulant/antiplatelet usage. In this article, we present the management of chronic SDH over a period of 15 months using the principles followed at our center. In 60 patients of chronic SDH, with the use of drains, we waited for radiological demonstration of brain expansion before drain removal and discharge. In our experience, this has led to better prognostication and very low recurrence rates, particularly in patients with comorbidities and on anticoagulant/ antiplatelet medication.
Keywords: burr hole; chronic SDH; drains; imaging; treatment